2022
DOI: 10.1186/s12877-022-03492-8
|View full text |Cite|
|
Sign up to set email alerts
|

The health equity characteristics of research exploring the unmet community mobility needs of older adults: a scoping review

Abstract: Background Unmet community mobility needs of older adults, published since the announcement of the UN sustainable development goals was synthesised to describe the health equity characteristics of research identifying unmet community mobility needs of older adults. Methods Searches were conducted in March and April 2020, 2275 articles were screened and 100 identified for data extraction. Results Findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(129 reference statements)
1
2
0
Order By: Relevance
“…Because of the insufficiency of available data, further exploration of the impact of outdoor mobility interventions on health equity was not possible. This is in accordance with a previous scoping review exploring health equity characteristics in studies of unmet community mobility needs for older adults, which identified poor inclusion and reporting of characteristics to evaluate and follow-up aspects of health equity in the evidence base(Biljon, 2022).The very low reporting of any potential harms (e.g., falls, hospitalization and mortality) in the included studies limits the completeness and usage of the evidence in decision-making. Eventhough a few studies transparently addressed potential harms of the interventions and found no substantial difference between intervention and control group, it is still uncertain of this is an accurate representation of the harms that outdoor mobility interventions might lead to based on risk of bias and underpowered studies to detect any differences.…”
supporting
confidence: 87%
“…Because of the insufficiency of available data, further exploration of the impact of outdoor mobility interventions on health equity was not possible. This is in accordance with a previous scoping review exploring health equity characteristics in studies of unmet community mobility needs for older adults, which identified poor inclusion and reporting of characteristics to evaluate and follow-up aspects of health equity in the evidence base(Biljon, 2022).The very low reporting of any potential harms (e.g., falls, hospitalization and mortality) in the included studies limits the completeness and usage of the evidence in decision-making. Eventhough a few studies transparently addressed potential harms of the interventions and found no substantial difference between intervention and control group, it is still uncertain of this is an accurate representation of the harms that outdoor mobility interventions might lead to based on risk of bias and underpowered studies to detect any differences.…”
supporting
confidence: 87%
“…Exploring older adults’ life space has value as it reflects their mobility and participation in society. A literature review (Van Biljon et al 2022 ) showed that published research on the unmet community mobility needs of older adults was predominantly from higher income countries. Identifying only one source from Africa, it concluded that peer-reviewed primary research on this subject does not reflect a global drive to end discrimination, exclusion and reduce the inequalities and vulnerabilities that leave people behind (Van Biljon et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…After publication of this article [ 1 ], the authors reported that in the abstract, paragraph Conclusions, the 3rd sentence should not start with “15”, but with “Fifteen years”.…”
mentioning
confidence: 99%